2014
DOI: 10.2298/bah1404661t
|View full text |Cite
|
Sign up to set email alerts
|

Comparitive study on the efficacy of ELISA and IS900 PCR for the diagnosis of Paratuberculosis in goats

Abstract: Paratuberculosis, one of the chronic granulomatous enteritis that predominantly affects ruminants worldwide, is caused by Mycobacterium avium subsp. paratuberculosis (MAP). It is most efficiently diagnosed by MAP from faeces by Polymerase Chain Reaction (PCR). Serological tests like Enzyme Linked Immuno Sorbent Assay (ELISA) also provides a rapid and cost-effective alternative diagnostic tool. Present study was carried out to directly evaluate the sensitivity and specificity of ELISA (ID vet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Out of them 155 animals reacted positively with ELISA, while 809 animals reacted negatively in the farm with a prevalence rate 16.1%. The prevalence of paratuberculosis was in parallel to that recorded by (Abraham et al, 2014) who reported that the prevalence of paratuberculosis among dairy cattle was (16%). In another side, the obtained results are different from the result obtained by (Fawzy et al, 2013), who found that, the highest prevalence rate of the disease among the examined farms, that may be attributed to size of sample collected and method of diagnosis and the prevalence rate was 46.6%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Out of them 155 animals reacted positively with ELISA, while 809 animals reacted negatively in the farm with a prevalence rate 16.1%. The prevalence of paratuberculosis was in parallel to that recorded by (Abraham et al, 2014) who reported that the prevalence of paratuberculosis among dairy cattle was (16%). In another side, the obtained results are different from the result obtained by (Fawzy et al, 2013), who found that, the highest prevalence rate of the disease among the examined farms, that may be attributed to size of sample collected and method of diagnosis and the prevalence rate was 46.6%.…”
Section: Discussionsupporting
confidence: 78%
“…Despite of low sensitivity and specificity, ELISA is considered a method of choice for diagnosis of Johne's disease positive herds. This is due to the ease of sample collection, rapid procedure, low cost and possibility of testing a large number of samples in a short time (Abraham et al, 2014;Gupta et al, 2012). A total number of 964 animals tested by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA is considered a method of choice for diagnosis of Johne's disease in positive herds. This is due to the ease of sample collection, rapid procedure, low cost and possibility of testing a large number of samples in a short time (Gupta et al, 2012;Abraham et al, 2014;Ali et al, 2019;Selim and Ali, 2020).…”
Section: Discussionmentioning
confidence: 99%